(untitled) (KULT_online, 2012)
The monograph Literatur im Jahrhundert des Auges. Realismus und Fotografie im bürgerlichen Zeitalter (Literature in the Century of the Eye: Realism and Photography in the Bourgeois Era), published in 2010 by Sabina Becker, is a study of realistic literature and its relation to photography, which here reveals itself through calm convergence and integration and not through a disregarding hush, as has long been maintained. A structural analogy is seen between literature and photography, concerning as much the experience of time as the experience of seeing, because a changed perception led to a development of a ’photographic gaze’. In mostly convincing argumentation, theses and thoughts are developed in close reliance on the primary literature, and founded in the research area ’Literature and Visuality’.